Toxicity of aqueous extract of Stevia rebaudiana in Rattus norvegicus variety Sprague Dawley - Julio Alberto Todco Palza (2019)
The toxicity of the aqueous extract of Stevia rebaudiana in Rattus norvegicus variety Sprague Dawley was evaluated for 60 days. It was held at the Biology Biology UNSA, Arequipa, during the months August to December 2012 16 Rattus norvegicus Sprague Dawley variety distributed in four groups of 4 rats each were used: The distilled water (Control Group) was administered to the control group, the Stevia rebaudiana aqueous extract was administered to the orogastric group experimentally 2, 3, 4 doses of 0.3, 0.6 and 0.9 g / kg / day respectively. Wierner's kits were used for the determination of TGO, TGP, glucose and creatinine. Body weight was measured on an Omni 5300 digital scale. The tissues evaluated (liver, kidney and stomach) by the Harris method. There was no significant difference in the activity of TGO and TGP in plasma of Rattus norvegicus variety Sprague Dawley with treatment of aqueous extract of Stevia rebaudiana in doses of 0.3, 0.6 and 0.9 g / kg / day for 60 days (p> 0.05). There was a significant decrease in plasma glucose levels of Rattus norvegicus Sprague Dawley variety with treatment of aqueous extract of Stevia rebaudiana in doses of 0.3, 0.6 and 0.9 g / kg / day for 60 days (p> 0.05). There was no significant difference in creatinine levels in treatments with aqueous extract of Stevia rebaudiana 0.3, 0.6 and 0.9 g / kg / day with respect to the control group (p> 0.05). A significant decrease was found in the body weight of the rats treated with aqueous extract of Stevia rebaudiana 0.3, 0.6 and 0.9 g / kg / day with respect to the control group (p <0.05). No microscopic alteration was found in Liver, kidney and stomach of Rattus norvegicus Sprague Dawley variety with treatment of aqueous extract of Stevia rebaudiana in doses of 0.3, 0.6 and 0.9 g / kg / day for 60 days.